Effects of visual adaptation on perception of and satisfaction with own body size: two randomised studies. (13th November 2015) - Bould, Helen; Carnegie, Rebecca; Allward, Heather; Bacon, Emily; Lambe, Emily; Sapseid, Megan; Button, Katherine; Lewis, Glyn; Skinner, Andy; Broome, Matthew; Park, Rebecca; Harmer, Catherine; et al.
Abstract: Background: Body dissatisfaction is prevalent among women and predicts eating disorders and obesity. Visual adaptation to pictures of underweight or overweight bodies changes body size perceived as normal in others. We aimed to test the hypothesis that exposure to images of underweight or overweight bodies would change perception of and satisfaction with own body size. Methods: We recruited female students and staff aged 18–25 years from the University of Bristol via posters and emails. In study 1, participants had normal body-mass index (BMI) (19–25 kg/m 2 ). In study 2, they had normal BMI and also high body dissatisfaction (defined as a score of >35 on the Body Dissatisfaction subscale of the Eating Disorder Inventory). Both studies had 80% power to detect an effect size of 0·36 (p=0·05). A computer-generated random sequence randomised participants into three groups, according to which category of images they would see. Participants and experimenters were masked to randomisation; and participants were unaware of the study purpose. Participants completed a 15 min adaptation task consisting of their looking at photographs of women of the same age group altered by the authors to appear slightly underweight, normal weight (control group), or slightly overweight Participants then looked at themselves in a mirror. Visual analogue scale (VAS) scores were taken before adaptation and again after adaptation and looking in the mirror. The analysis compared post-adaptation scores adjusted for pre-adaptation scores. We measured perceived size (primary outcome) and satisfaction with size (secondary outcome) and analysed data by intention to treat using linear regression, adjusting for baseline. Ethics approval for both studies was given by the Faculty of Science Research Ethics Committee, University of Bristol. Participants gave consent after being informed about the task they would complete. Findings: We recruited 90 women between Nov 11, 2012, and Dec 16, 2013 in study 1; and 93 women (July 29, 2014, to Aug 8, 2015) in study 2. After adaptation, for every VAS point increase in group (underweight 0, normal 1, overweight 2), perceived own size post adaptation decreased by 2·2% (95% CI −4·1 to −0·3, p=0·02) in study 1, and 2·8% (–5·1 to −0·4, p=0·02) in study 2. Satisfaction with size increased by 1·5% (95% CI −0·9 to 3·9, p=0·21) in study 1 and 5·7% (2·3 to 9·0, p=0·001) in study 2. Participants shown underweight images subsequently perceived themselves as larger and were less satisfied. Interpretation: These findings suggest that, in young women, exposure to underweight images (frequently depicted in the media) changes perception of own body size and increases body dissatisfaction. This automatic mechanism could be targeted at a public health level by advocating replacement of underweight images with normal weight images. Such an intervention could reduce body dissatisfaction in normal weight women and possibly rates of eating disorders and obesity. Funding: Study 1 was unfunded. For study 2, HB was funded by an Elizabeth Blackwell Clinical Primer (Wellcome Trust Strategic Support Fund) from April to September, 2014, and subsequently as a Wellcome Trust Doctoral Training Fellow (October, 2014, to the present).